2019
DOI: 10.1073/pnas.1904159116
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contribution of sequence variants with regulatory and evolutionary significance to 34 bovine complex traits

Abstract: Many genome variants shaping mammalian phenotype are hypothesized to regulate gene transcription and/or to be under selection. However, most of the evidence to support this hypothesis comes from human studies. Systematic evidence for regulatory and evolutionary signals contributing to complex traits in a different mammalian model is needed. Sequence variants associated with gene expression (expression quantitative trait loci [eQTLs]) and concentration of metabolites (metabolic quantitative trait loci [mQTLs]) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(170 citation statements)
references
References 71 publications
5
148
4
Order By: Relevance
“…That is, the average number of traits affected by a single-nucleotide polymorphisms (SNP) in this group is 9.63. Additional analysis with functional data 12,13 indicated that both single-trait and multi-trait FDRed can help find informative variants at lenient p value thresholds where conventional FDR was large (Supplementary Note 1). When imposing a significance threshold in only one sex, at the multitrait p value threshold of 1e−6, the multi-trait FDRed was 0.14 in bulls and 0.2 in cows (Supplementary Data 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the average number of traits affected by a single-nucleotide polymorphisms (SNP) in this group is 9.63. Additional analysis with functional data 12,13 indicated that both single-trait and multi-trait FDRed can help find informative variants at lenient p value thresholds where conventional FDR was large (Supplementary Note 1). When imposing a significance threshold in only one sex, at the multitrait p value threshold of 1e−6, the multi-trait FDRed was 0.14 in bulls and 0.2 in cows (Supplementary Data 5).…”
Section: Resultsmentioning
confidence: 99%
“…All calculations regarding this clustering were done separately in each sex. Firstly, variants were ranked by their multi-trait p values adjusted (divided) by their functional-and-evolutionary trait heritability (FAETH) score 13 . Then, variants ranked within the top 10% within each sex were selected for LD pruning, using Plink 1.9 38 measured as the correlation between the genotypes of variant i and variant j .…”
Section: Methodsmentioning
confidence: 99%
“…A 1 Mbp region nearby DGAT1 harbors three polymorphisms that are able to explain a high amount of the SNP variance in the set. Xiang et al [40] classified 17,669,372 imputed variants into 30 sets of markers. This classification included categories such as inter-species conserved markers, polymorphisms associated with metabolic traits (several milk metabolites), expression regulation related polymorphisms (gene and exon expression QTLs, sQTLs, and allele-specific expression QTLs), and markers with evolutionary roles.…”
Section: Applicability Of the Present Results And Future Analysismentioning
confidence: 99%
“…Yet understanding how those genomes work without ENCODE scale projects for each species will require that we use evolutionary approaches to identify key functional regions. DNA sequences subject to purifying selection across different species reflect functional constraints (Xiang et al 2019;Finucane et al 2015). The detection of conserved non-coding sequence (CNS) in plants is an ongoing challenge(Van de Velde et al 2016) and recent studies (Tu et al 2020;Ricci et al 2019;Lu et al 2019) could provide new insight into their function.…”
Section: Introductionmentioning
confidence: 99%